Evidence for Whole Mantle Convection Driving Cordilleran Tectonics. Issue 8 (29th April 2019) - Spencer, C. J.; Murphy, J. B.; Hoiland, C. W.; Johnston, S. T.; Mitchell, R. N.; Collins, W. J.
Abstract: Deducing mechanisms for advance and retreat of magmatic arcs is fundamental to understanding accretionary tectonics and the evolution of continents. However, first‐order explanations of large spatial and long temporal changes in magmatic arcs remain elusive. We present isotopic evidence that Cordilleran magmatic arc systems were controlled by spherical harmonic degree‐2 mantle convection and characterized by two antipodal upwellings bisected by a meridional downwelling. Once established, the meridional "subduction girdle" drives hemispheric slab rollback and remains the locus of Cordilleran oceanic arcs. Continual westward migration of the North and South American continents led to arc advancement and consumption of back‐arc basins, culminating in arc‐continent collisions and reversals of subduction polarity. Continental arcs initiated diachronously as North and South America arrived at the subduction girdle and oceanic arcs were accreted. Systematic patterns in radiogenic isotopes along the Cordilleran system support that slab dynamics are controlled, to first order, by long‐wavelength mantle convection. Plain Language Summary: The migration of modern volcanic arcs has been demonstrated by geophysical methods to be controlled by mantle convection patterns. It is hypothesized that like an inverted sail, subducted oceanic slabs "blow in the mantle wind." However, identifying geologic data supporting the long term and widespread migration patterns has remained elusive. Luckily, the geochemical signature of oceanic and continental arcs is controlled by the amount of continental material assimilated in the magmas and therefore can be distinguished by distinct signatures. We demonstrate a consistent evolution of the geochemical signature of the Cordilleran subduction system from Antarctica to northeast Russia that attests to a dramatic migration of subduction zone magmatism from a continental to oceanic position and then back to a continental position within the past ~150 Myr. These data suggest that volcanic arc migration is controlled at the first‐order by large‐scale and long‐lived mantle convection patterns. Key Points: Migration of arc systems to meridional downwelling is driven by large‐scale mantle convection and outpaces continental drift Radiogenic isotopic signatures suggest that arc migration to downwelling marks transition from continental to oceanic arcs Oceanic arc accretion and beginning of renewed continental arc magmatism begins as continents override downwelling